In Vivo Imaging of Mouse Tumors by a Lipidated Cathepsin S Substrate1. Issue 29 (30th May 2014) - Hu, Hai‐Yu; Vats, Divya; Vizovisek, Matej; Kramer, Lovro; Germanier, Catherine; Wendt, K. Ulrich; Rudin, Markus; Turk, Boris; Plettenburg, Oliver; Schultz, Carsten
Abstract The synthesis and evaluation of two cathepsin S‐specific probes is described. For long‐term retention of the probe at the target site and a high signal‐to‐noise ratio, we introduced a lipidation approach via the simple attachment of palmitoic acid to the reporter. After cathepsin S‐specific cleavage in cultured cells and in a grafted tumor mouse model, fluorescence increased owing to dequenching and we observed an intracellular accumulation of the fluorescence in the target tissue. The lipidated probe provided a prolonged and strongly fluorescent signal in tumors when compared to the very similar non‐lipidated probe, demonstrating that non‐invasive tumor identification is feasable. The homing principle by probe lipidation might also work for selective administration of cytotoxic compounds to specifically reduce tumor mass.